2023
DOI: 10.1021/acs.orglett.3c00865
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Catalyzed Photodriven Stereoselective Hydrodifluoroacetylative Cyclization of Alkyne

Abstract: A metal-free protocol for visible-light-driven intramolecular hydrodifluoroacetylative cyclization of N-propargyl or N-homopropargyl-2-bromo-2,2-difluoroacetamide to α,α-difluorinated β-substituted γ- or δ-lactam without an additional photosensitizer has been developed. By using thiol and Hantzsch ester as the catalyst and hydrogen donor, respectively, to implement a hydrogen atom transfer process, moderate to high (Z) selectivity was achieved. The results of a mechanistic investigation revealed the critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, these reports are restricted by the relatively narrow scope of substrates. In recent years, an increasing interest in radical cyclization reactions has led to the development of efficient protocols to synthesize various functionalized α,α-difluoro-γ-lactams through radical-mediated processes. For instance, radical cascade cyclization of alkenes catalyzed by transition metals, such as copper, nickel, and palladium, was developed to rapidly assemble CF 2 -decorated γ-lactams. Furthermore, Zhu et al demonstrated a novel photoredox/iodide catalytic system toward these compounds via aminodifluoroalkylation of alkenes (Scheme a1) .…”
Section: Introductionmentioning
confidence: 99%
“…However, these reports are restricted by the relatively narrow scope of substrates. In recent years, an increasing interest in radical cyclization reactions has led to the development of efficient protocols to synthesize various functionalized α,α-difluoro-γ-lactams through radical-mediated processes. For instance, radical cascade cyclization of alkenes catalyzed by transition metals, such as copper, nickel, and palladium, was developed to rapidly assemble CF 2 -decorated γ-lactams. Furthermore, Zhu et al demonstrated a novel photoredox/iodide catalytic system toward these compounds via aminodifluoroalkylation of alkenes (Scheme a1) .…”
Section: Introductionmentioning
confidence: 99%
“…10 To the best of our knowledge, photoredox cyclisations 11,12 of this type have not been previously described as such reactions could be complicated by competing redox-triggered C–H functionalization reactions adjacent to nitrogen. 13 Related work has circumvented this problem by using redox inert sulfonamides 14,15 or amides 16–21 as cyclisation substrates, but subsequent deprotection or redox adjustments are then required to access synthetically useful products. Here we show that cyclisation of unprotected β-bromodifluoroalkyl amines prepared from readily available amines, aldehydes and carboxylic acids 22 is indeed possible resulting in a concise synthesis of cyclic β-fluoroalkyl amines (Fig.…”
mentioning
confidence: 99%
“…Therefore, the preparation of F-containing γ-lactams may be helpful to identify compounds with more attractive properties in drug discovery, and many studies have focused on the construction of this structural unit. Examples include intramolecular cyclization of difluoropentenamide, aminodifluorobutanoate, N -allylbromodifluoroacetamide (Scheme , (1)), and N -propargylbromodifluoroacetamide (Scheme , (2)); intermolecular cyclization between alkenes and α-bromodifluoroacetamides (Scheme , (3)); intramolecular radical cyclization of N -allylhalodifluoroacetamides (Scheme , (4)) . However, these procedures lack the generality of the starting reaction materials, which limits their applications.…”
mentioning
confidence: 99%